1966
DOI: 10.1111/j.1399-6576.1966.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of pH of Human Erythrocyte From the Distribution of 5,5‐Dimethyl‐2,4‐Oxazolidinedione (DMO)

Abstract: SUMMARY The intracellular pH of human erythrocytes in nine subjects was calculated by the DMO method and compared with direct measurements on the hemo‐lysate. The standard deviation of differences between means of duplicate observations of the two methods was ± 0.111 pH unit. The amount of DMO‐like substance in normal human blood was found to vary from one subject to another and must be taken into account in the calculations. It is concluded that the DMO method is of limited accuracy in estimating intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

1968
1968
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
1
1
1
Order By: Relevance
“…Substantially similar results have been reported in man [Thomason, 1963;Paymaster and Englesson, 1966] and in the rat [Sanslone and Muntwyler, 1964]. In contrast, when human red cells are equilibrated with DMO in vivo, erythrocyte pH is approximately 7 09 [Bromberg, Theodore, Robin and Jensen, 1965].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Substantially similar results have been reported in man [Thomason, 1963;Paymaster and Englesson, 1966] and in the rat [Sanslone and Muntwyler, 1964]. In contrast, when human red cells are equilibrated with DMO in vivo, erythrocyte pH is approximately 7 09 [Bromberg, Theodore, Robin and Jensen, 1965].…”
Section: Discussionsupporting
confidence: 68%
“…Although several authors have suggested that measurements of erythrocyte pH based on the distribution of DMO are of doubtful value [Sanslone and Muntwyler, 1964;Funder and Wieth, 1966;Paymaster and Englesson, 1966;Bittar, 1967], the results of the current studies do not support this view. In the present series of experiments, the mean distribution ratios for hydrogen and chloride ions between erythrocytes and phosphate buffer were identical, and the values were consistent with recent determinations of the membrane potential of mammalian red cells [Lassen and Sten-Knudsen, 1968;Jay and Burton, 1969].…”
Section: Discussioncontrasting
confidence: 57%
“…Both the potentiometric and the DMO method can be carried out simultaneously on the same specimen material, without the results being subject to the same sources of error. When the DMO method was first introduced for meäsüring the pH value of erythrocytes, only a few coniparative studies with the potentiometric method were carried out, and these did not show a satisfactory agreement (6,7). Meanwhile, the analytical techniques for both methods have undergone further development.…”
Section: Introductionmentioning
confidence: 99%